PENGARUH PERHATIAN ORANG TUA TERHADAP MOTIVASI BELAJAR - Nidaul Hasanah; Nadiah Nadiah (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2023)
This research is motivated by one of the factors for the growth of learning motivation that can encourage from outside and from within a person to be able to do a good action, namely less than optimal parental attention. Supervision and direction from parents will affect children in following lessons at school. This research aims: to measure how much influence parental attention has on learning motivation at MI Al-Hidayah UKA. The method used is a type of Quantitative Research with a Descriptive Correlational Analytic method. Sampling technique using Simple random sampling, with a total of 57 students. The results showed that when viewed in terms of coefficient tests Product Moment produce " " or " " is 0.505, while "rt" at a significant level of 5% = 0.254 and a significant level of 1% = 0.330. Thus it can be accepted and approved, while the Null Hypothesis (Ho) is rejected or disapproved. Based on the results of this study, it can be concluded that there is an influence on parents' attention to learning motivation.